Trp Channels in Cold Transduction - Ugarte-Martinez, G; Madrid-Montecinos, R; Gonzalez-Figueroa, A; Pertusa-Pastor, M; Piña-Muñoz, R (Springer International Publishing, 2015)
In the somatosensory system, cold thermoreceptor neurons and cold nociceptors are responsible for the detection of environmental low temperatures. The underlying machinery is far from simple; it is a result of the participation of several classes of transduction and voltage-gated ion channels that functionally coexist to give shape to the cold-induced receptor potential and subsequent action potential firing in response to cold stimulation. The cold-induced electrical responses begin in the free nerve endings of these sensory neurons, where a subgroup of thermosensitive Transient Receptor Potential channels (thermoTRPs) plays a critical role. These channels have evolved as molecular thermal sensors activated by a wide range of cold temperatures, and they have been proposed as key elements of the transduction machinery responsible for detection of environmental cold in primary somatosensory neurons. In this chapter, we summarize the most important functional properties of the primary sensory neurons involved in cutaneous cold detection, and the corresponding role of the thermoTRP channels TRPM8, TRPA1 and TRPC5 in cold transduction. © Springer International Publishing Switzerland 2016. All rights reserved.